2007
DOI: 10.3750/aip2007.37.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fermented fish offal in formulated diet of the Indian major carp, rohu, Labeo rohita (Hamilton)

Abstract: . 2007. Evaluation of fermented fish offal in formulated diet of the Indian major carp, rohu, Labeo rohita (Hamilton). Acta Ichthyol. Piscat. 37 (2): 99-105.Background. Carp fish offal contains high amount of protein and lipid. The quest for protein sources alternative to fish meal has been a priority in aquaculture research because of growing concerns on the future availability of fish meal for incorporation in fish diets. This study determined the extent to which carp fish offal could be fermented and used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The technique allows comparatively higher inclusion levels (30-40%) of oilseed meals, legumes and aquatic macrophytes compared to non-fermented raw meals (10-20%) in the diets of L. rohita (Mukhopadhyay & Ray 1999;Bairagi et al 2002;Ramachandran & Ray 2007). The results in the present study is in harmony with the previous studies, reported that 30-50% FM protein could be replaced with fermented fisheries by-products and plant protin from the diets of L. rohita, H. fossilis, O. niloticus and P. major (Fagbenro et al 1994;Mondal et al 2007Mondal et al , 2008Kader et al 2011). Reduction in FI with the increasing FM replacement levels were attributed for the reduced growth performance in Japanese flounder (Deng et al 2006;Uyan et al 2006).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The technique allows comparatively higher inclusion levels (30-40%) of oilseed meals, legumes and aquatic macrophytes compared to non-fermented raw meals (10-20%) in the diets of L. rohita (Mukhopadhyay & Ray 1999;Bairagi et al 2002;Ramachandran & Ray 2007). The results in the present study is in harmony with the previous studies, reported that 30-50% FM protein could be replaced with fermented fisheries by-products and plant protin from the diets of L. rohita, H. fossilis, O. niloticus and P. major (Fagbenro et al 1994;Mondal et al 2007Mondal et al , 2008Kader et al 2011). Reduction in FI with the increasing FM replacement levels were attributed for the reduced growth performance in Japanese flounder (Deng et al 2006;Uyan et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…; Fagbenro & Jauncey ). Mondal, Kaviraj, Mukhopadhyay, Datta and Sengupta () and Mondal et al . () reported that fermented fish offal, mustard oil cake and rice bran mixture could replace 50% FM protein from the diets of Indian major carp and catfish, Heteropneustes fossilis .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results are in accordance with a previous report by Sun et al [8], who found that fermented fisheries by-products and soybean curd residues could replace up to 30% FM protein in diet of juvenile Japanese flounder. It has also been reported that 50% FM protein can be replaced with fermented fish offal, mustard oil cake, and rice bran mixture in diets of Indian major carp (L. rohita) and freshwater catfish (H. fossilis) [9,10]. Codried fermented fish silage and soybean meal can also partially replace FM protein in tilapia and catfish diets [4,11].…”
Section: Discussionmentioning
confidence: 96%
“…It is also a useful technique for drying wet product with minimal nutrient loss [7]. Sun et al [8] reported that fermented fisheries byproducts and soybean curd residues mixture could replace 30% FM protein from diets of Japanese flounder Paralichthys olivaceus, while in freshwater fish (Labeo rohita and Heteropneustes fossilis) 50% FM protein could be replaced with fermented fish offal, mustard oil cake, and rice bran mixture [9,10]. Codried fermented fish silage and soybean meal was also found to be a suitable protein supplement in diets of catfish Clarias gariepinus and Nile tilapia Oreochromis niloticus [4,11].…”
Section: Introductionmentioning
confidence: 98%